A novel technique to predict harmonic response of Particle-damping structure based on ANSYS® secondary development technology. (August 2018) - Zhang, Renliang; Wu, Chengjun; Zhang, Yantong
Highlights: A novel technique is developed in this paper to predict harmonic response of particle-damping structure with required accuracy. ANSYS ® secondary development technology and iterative solution method are used as the approach to solving the solutions of highly nonlinear particle-damping structure based on ANSYS ® . To make it convenient and repeatable to conduct harmonic analysis of particle-damping structure, module is developed and interfaces are created. Comparing to previous methods, this novel technique works with higher efficiency and consumes much less computational expenses including computing time and computer resources (CPU and Memory). Abstract: Since the particle damping is highly developed and widely used to suppress the structure vibration and a more efficient and accurate technique for predicting the harmonic responses of particle-damping structure is in need, this paper presents a novel technique to predict the harmonic response of particle-damping structure based on iterative solution method and ANSYS ® secondary development technology. In order to establish the iteration solution method for predicting the harmonic response of particle-damping structure, iteration scheme of particle-damping structure (system) is derived from the mechanical dynamic formulae and particle damping formulae. For single or multiple degree of freedom system, basic solutions of each iteration cycle are solved by mathematical model, while the solutions of continuous systems are solved by ANSYS ® in this paper. To conduct harmonic analysis of highly nonlinear particle-damping system in ANSYS ®, iterative solution method (i.e. iteration scheme) is coded into program by ANSYS ® Parametric Design Language (APDL). Based on the code, module of particle damping is developed and interfaces are created in ANSYS ® using User Interface Design Language (UIDL). To verify the accuracy of the novel technique, two research cases are detailed introduced and frequency response functions (FRFs) of acceleration are obtained by simulations and experiments. It's worthwhile to note that simulation results have excellent consistency with the experiment results. In addition, the simulations conducted by ANSYS ® using iteration solution method developed in this paper is more efficient and consumes less computer resources than previous methods. Consequently, both accuracy and higher efficiency of the novel technique are guaranteed.